Legal Responsibility of the Penghulu in Same Sex Marriage Involving Fake Identity in Batam City - Widarto, Muhammad; Rina S. Shahrullah; Elza Syarief (Istinbath : Jurnal Hukum, 2025)
Marriage is a physical and emotional bond between a man and a woman that aims to build a happy, lasting family. Such a bond should be seen not only as a way of satisfying biological need, but also as the marriage’s purpose to produce offspring. This research aims to analyze the legal responsibility of the Head of the Religious Affairs Office (KUA) and the Penghulu in Sei Beduk Sub-district, Batam City, for same-sex marriage involving fake identities. Then, what is the legal status of such marriages, and what legal remedies can be pursued? This research uses a field study method with an empirical juridical approach. Primary data was obtained from the Head of KUA and Penghulu in Sei Beduk Sub-district, Batam City. Secondary data were obtained from relevant books, journal articles, theses, and dissertations. The data were collected through interviews and documentation and analyzed using a qualitative-inductive method. The results show that same-sex marriages are invalid in terms of religious norms, and do not fulfill the requirements of the applicable laws and regulations. In terms of culture and noble values that live in the soul of the Indonesian nation, similar marriages are also seen as contradictory. To demonstrate legal responsibility, the Head of KUA/Penghulu of Sei Beduk Subdistrict, Batam City, as an interested party, has applied to the Religious Court of Batam City for the annulment of the marriage after realizing that it was defective under Islamic law and national legislation. In the decision of the Batam City Religious Court No. 60/Pdt.G/2013/PA.Btm, the same-sex marriage that took place at the KUA of Sei Beduk Subdistrict, Batam City, was finally annulled, resulting in the status of the marriage being deemed nonexistent.